Effect of grain processing at different barley varieties on nutrient compositions, starch contents and in vitro digestion parameters - Güney, Mehtap (Progress in Nutrition, 2019)
This study examined how response of treating with heat of twelve different barley varieties on nutrient composition, starch contents, in vitro dry matter digestibility (IVDMD) and in vitro organic matter digestibility (IVOMD). In the study, a total of twelve different barley varieties (Tarm-92, Avcı-2000, Çetin-2002, Özdemir, İnce, Bolayır, Anka-04, Tosunpaşa, Larende, Martı) were used. Processing with heat to all barley varieties were significantly higher contents of DM, OM and neutral detergent fiber (NDF). However, starch contents were significantly lower compared to unprocessing group (p